IDENTIFIKASI PAJAK POTENSIAL DI KABUPATEN PEMALANG (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aims to determine the type of local tax potential in terms of contribution, growth and elasticity to Total Tax Areas that form the Local Revenue. The data used are secondary data in Pemalang District Government with the study period of 2010 - 2014. The analysis technique used is the contribution analysis, analysis of growth and elasticity by considering the standard deviation. Results showed that the types of local taxes related to economic activity is indicated as a potential tax that has stability in all three indicators, namely the restaurant tax, advertisement tax and entertainment tax. Keywords: Identification of Potential Taxes, The Autonomous Region